Global genetic diversity of var2csa in Plasmodium falciparum with implications for malaria in pregnancy and vaccine development. Issue 1 (December 2018) - Benavente, Ernest; Oresegun, Damilola; Sessions, Paola; Walker, Eloise; Roper, Cally; Dombrowski, Jamille; Souza, Rodrigo; Marinho, Claudio; Sutherland, Colin; Hibberd, Martin; Mohareb, Fady; Baker, David; et al.
Abstract Malaria infection during pregnancy, caused by the sequestering ofPlasmodium falciparum parasites in the placenta, leads to high infant mortality and maternal morbidity. The parasite-placenta adherence mechanism is mediated by the VAR2CSA protein, a target for natural occurring immunity. Currently, vaccine development is based on its ID1-DBL2Xb domain however little is known about the global genetic diversity of the encodingvar2csa gene, which could influence vaccine efficacy. In a comprehensive analysis of thevar2csa gene in >2, 000 P. falciparum field isolates across 23 countries, we found thatvar2csa is duplicated in high prevalence (>25%), African and Oceanian populations harbour a much higher diversity than other regions, and that insertions/deletions are abundant leading to an underestimation of the diversity of the locus. Further, ID1-DBL2Xb haplotypes associated with adverse birth outcomes are present globally, and African-specific haplotypes exist, which should be incorporated into vaccine design.